Outbreak of Salmonella Newport associated with internationally distributed raw goats' milk cheese, France, 2018. (2020) - Robinson, E.; Travanut, M.; Fabre, L.; Larréché, S.; Ramelli, L.; Pascal, L.; Guinard, A.; Vincent, N.; Calba, C.; Meurice, L.; Le Thien, MA.; Fourgere, E.; et al.
Abstract: Raw milk cheeses are commonly consumed in France and are also a common source of foodborne outbreaks (FBOs). Both an FBO surveillance system and a laboratory-based surveillance system aim to detect Salmonella outbreaks. In early August 2018, five familial FBOs due to Salmonella spp. were reported to a regional health authority. Investigation identified common exposure to a raw goats' milk cheese, from which Salmonella spp. were also isolated, leading to an international product recall. Three weeks later, on 22 August, a national increase in Salmonella Newport ST118 was detected through laboratory surveillance. Concomitantly isolates from the earlier familial clusters were confirmed as S. Newport ST118. Interviews with a selection of the laboratory-identified cases revealed exposure to the same cheese, including exposure to batches not included in the previous recall, leading to an expansion of the recall. The outbreak affected 153 cases, including six cases in Scotland. S . Newport was detected in the cheese and in the milk of one of the producer's goats. The difference in the two alerts generated by this outbreak highlight the timeliness of the FBO system and the precision of the laboratory-based surveillance system. It is also a reminder of the risks associated with raw milk cheeses.